Upaya Meningkatkan Pemahaman Siswa Tentang Garis Bilangan dengan Menggunakan Kartu Bilangan di SDN 32 Ampenan - I Gede Saputra (Universitas Pendidikan Mandalika, 2020)
The purpose of this study was to improve students' understanding of the number lines by using number cards in grade III students of SDN 32 Ampenan. This research uses classroom action research methods. The research instruments used in this study were observation sheets and question sheets. The research data analysis technique used is quantitative descriptive analysis technique. The conclusions obtained from the results of this study are: (1) The use of number card learning aids can improve students' understanding of class III semester I of SDN 32 Ampenan. This is based on the results of the first and second cycle tests. In the first cycle, the average student learning outcomes were 56.67 with 22 students (52.38%) complete and 20 students (47.62%) did not complete the study with a good enough understanding category and in the second cycle the average learning outcomes 67.38 students with 34 students (80.95%) complete and 8 students (19.05%) did not complete study in the good understanding category. (2) The results of observing student activities in the first cycle of two meetings are in the active category and in the second cycle the category is very active. While the observations of teacher activity in the first cycle of two meetings were in the very active category and in the second cycle the category was very active.